Investigation of burr in high speed microdrilling - Ali, Mohammad Yeakub; Mohamed, Abd. Rahman; Fadila, N.; Hannah, N. (Trans Tech Publications Ltd., Switzerland, 2013)
This paper discusses burr in microdrilling that affect forms and functions of parts. The effects of microdrillingparameters on burr length and width are identified. The experiment was conducted using Mikrotools DT110 machine with one millimetre diameter of HSS on copper workpiece. Burr heights in terms of burr length and burr width were measured by using scanning electron microscope. The data was analyzed using Taguchi method to find the optimum microdrilling process parameter for minimizing the burr height. The relationship among spindle speed, feed rate and burr has been developed. It is found that feed rate is the most influential factors on the burr height. The desirability of getting the minimum burr height is72% and the optimum parameters are 30000 rpm spindle speed and 0.2 mm/min feed rate.